Conhecimento e uso efetivo da avifauna em uma comunidade no entorno da Floresta Nacional do Araripe - FLONA, Barbalha - CE - TEIXEIRA, Pedro Hudson Rodrigues (2013)
This study was conducted in a community located within Araripe National Forest (Floresta Nacional do Araripe – FLONA) was to verify and claim the attractive features of the birds that call the attention of local experts, the types of birds captured and types of use. Interviews were conducted with 19 informants experts who held knowledge about birds, between the months of September 2012 to May 2013, identified by the “snowball” technique. The interviews were semi-structured and recorded, and included identifying the birds by photos (Checklist). The appealing characteristics that most attract the informants are the birds’ singing, followed by the beauty of their plumage; their potential for being hunted was another characteristic that appealed to the informants. The participants cited 98 species of birds from 32 families, which constituted 50.7% of the species in that region. The birds are used in three ways: consumption, breeding and for medicinal purposes. Consumption is the activity most frequently mentioned by the informants, and which includes the greatest number of species, ten of which stand out with greater UV – those which possess the characteristic of a high potential for being hunted. In terms of breeding, three stand out with greater UV – those which possess a singing characteristic. Three species of birds were mentioned as being used for medicinal purposes: Cyanocorax cyanopogon, which is used whole for speech problems; the feathers of Crypturellus noctivagus, for snakebites; and Crotophaga ani, used whole for treating “heavy cough”. Thus, knowledge of the medicinal use of birds in the semi-arid region of Brazil provide a relevant contribution to the phenomenon of zootherapy, by providing opportunities for discussions on conservation biology and sustainable use of natural resources, and by defining the best strategies to be adopted by environmental agencies to ensure the survival both of the species of birds used and of the communities that depend on them.